Cell-membrane coated nanoparticles: Role of machine learning and applications in diagnosis and therapy - Lulin Chen; Fei Lv; Yinsheng Cai; Jianbo Feng; Zhusheng Guo; Shaohong Li (Alexandria Engineering Journal)
The advancement of biomedical technologies has introduced a promising approach for targeted drug delivery—utilizing nano and microscale systems. These compounds provide the potential for precise drug delivery to specific tissues, enhancing diagnostic accuracy and therapeutic efficacy, thereby minimizing off-target effects and improving site-specific accumulation. They enable controlled release of therapeutic agents, reducing the systemic toxicity often associated with conventional drugs. This review particularly highlights the critical role of cell membrane-decorated nanocompounds (CDCs), which represent a significant innovation in this field. Artificial Intelligence (AI) plays a pivotal role in enhancing the precision of CDCs, utilizing advanced algorithms to predict optimal delivery routes and release mechanisms. Moreover, AI-driven analytics are instrumental in the real-time monitoring and adjustment of drug release rates, ensuring maximum efficacy and patient safety. This review delves into the applications of CDCs, exploring their characterization, drug delivery potential, and future prospects, with a specific focus on how cell membrane coatings can revolutionize the landscape of drug delivery. Furthermore, the integration of AI in these processes is emphasized, particularly in how it can significantly impact future therapeutic strategies.